A Comprehensive Insight Into Primary Intimal Sarcoma of the Pulmonary Artery; From Diagnosis to Management: A Case Report and Review of the Literature - Azin Alizadehasl; Soroush Najdaghi; Maryam Mohseni Salehi; Shahla Meshgi; Seyedeh Fatemeh Hosseini Jebelli; Azam Yalameh Aliabadi; Hoda Hakimian; Sara Forati; Amineh Safavirad; Delaram Narimani Davani (Clinical Case Reports)
ABSTRACT Primary intimal sarcoma of the pulmonary artery is a rare and aggressive malignancy that presents significant diagnostic and therapeutic challenges due to its nonspecific symptoms and propensity for late detection. This case report aimed to elucidate the diagnostic journey, surgical intervention, and multidisciplinary management of this rare entity. In September 2023, a 42‐year‐old male presented with dyspnea on exertion and retrosternal chest pain, classified as NYHA FC II. Initial investigations, including ECG and lab tests, indicated tachycardia and elevated troponin and NT‐pro‐BNP levels. Transthoracic and transesophageal echocardiography identified a multilobulated mass in the right ventricular outflow tract and main pulmonary artery. Cardiac MRI and CT angiography confirmed a high‐grade pleomorphic spindle cell tumor, leading to surgical resection in October 2023. Histopathology confirmed intimal sarcoma. Postsurgery, the patient underwent chemotherapy and radiotherapy, showing significant clinical improvement and no recurrence on follow‐up PET‐CT. This case highlights the importance of a multidisciplinary approach in diagnosing and managing primary intimal sarcoma of the pulmonary artery, emphasizing the role of advanced imaging, timely surgical intervention, and combined chemotherapy with radiotherapy in improving patient outcomes.